Tổng hợp một số 2-amino-6-aryl-4-(4’-hydroxy-n-metylquinolin-2’-on-3’-yl)pyrimidin - Toàn, Dương Ngọc; Anh, Trần Phương; Thảo, Nguyễn Minh (Vietnam Journal of Chemistry, 2017)
Six new 2-amino-6-aryl-4-(4’-hydroxy-N-methylquinolin-2’-on-3’-yl)pyrimidines have been synthesized from a,b-unsaturated ketones of 3-acetyl-4-hydroxy-N-methylquinolin-2-on by reaction of corresponding a,b-unsaturated ketones with guanidine chlorohydrate. The purity and structure of the obtained products have been confirmed by thin layer chromatography, IR, 1H NMR, 13C NMR, HSQC, HMBC and MS spectra. Keywords. Pyrimidines, methylquinolin, guanidine chlorohydrate, a,b-unsaturated ketones.